The impact on anxiety and depression of a whole school approach to health promotion: evidence from a Canadian comprehensive school health (CSH) initiative. Issue 4 (2nd October 2017) - Dassanayake, Wijaya; Springett, Jane; Shewring, Tania
Abstract: In this paper, we examine the impact of adopting a comprehensive school health (CSH) approach on reducing anxiety and depression of school-age children. We use the data from 245 schools that received government funding support to adopt a CSH approach in order to build health promoting school environments in Alberta. Using a linear multi-level (hierarchical) model, we compare the average percentage of students with anxiety and depression across the schools that are in three different funding stages: pre-funded, actively-funded, and post-funded. Results show that, all else held constant, the schools that are in the actively-funded stage, relative to pre-funded schools have a lower percentage of students who suffer from anxiety and depression.